Arithmetic textbooks panorama of the decade after the lifting of the ban on Lithuanian publications - Banionis, Juozas (Lietuvos matematikos rinkinys, 2023)
In 1904 with the lifting of the ban on Lithuanian publications by Russian czar government and in 1906 with giving the permit to teach arithmetics in mother tongue at primary schools the legal publishing of Lithuanian arithmetic textbooks started. Already in 1906 even three arithmetic textbooks were published. These were two parts of ``Arithmetic Taskbook“ by Pranas Mašiotas, the first part of ``Collection of Arithmetic Tasks and Examples“ by Petras Bendorius and Pranas Daugirda and two parts of translated from Polish ``Arithmetic Tasks and Examples“ by Stanislaw Thom. All the books step by step explained in the Lithuanian language four arithmetic operations up to ten, later a hundred and finally up to a thousand. In 1909 two important books were published: the second part of the textbook by Petras Bendorius and Pranas Daugirda and ``Elementary Arithmetics“ by Petras Mikolainis. The latter textbook could be distinguished for methodical instructions. In 1909–1916 Juozas Damijonaitis prepared and published two parts of ``Arithmetic Textbook“. The book was recompiled into three parts during the period of the Republic of Lithuania (in 1918–1940). It became popular and was constantly republished. When forming of arithmetic basics was coming to end in 1916 ``The Short Science of Arithmetics“ by S. Thom (1916) appeared in the Lithuanian language, where the theory of arithmetics was presented.